The prophenoloxidase from the wax moth Galleria mellonella: purification and characterization of the proenzyme - Kopácek, P; Weise, C; Götz, P (Insect biochemistry and molecular biology, 1995)
A prophenoloxidase (PPO) was purified from the hemolymph of the larvae of Galleria mellonella. A 135-fold purification of the proenzyme with 25% yield was achieved by a combination of different chromatographic methods. An alternative micropreparation of pure PPO by a novel method for native electrophoresis in polyacrylamide gel is also described. The molecular mass of the native PPO was estimated to be 300 kDa by the pore-limit gradient electrophoresis in polyacrylamide gel. In the presence of sodium dodecyl sulphate, two closely migrating subunits of 80 and 83 kDa were detected under non-reducing conditions. The PPO was shown to be a glycoprotein and its isoelectric point was 6.2. The amino-acid composition of the purified protein was similar to the PPO from Bombyx mori. The monospecific antibody raised against the purified PPO crossreacted with the (pro)phenoloxidase in hemolymph of Manduca sexta. The activation of the PPO with chymotrypsin was investigated and two proteins of 67 and 50 kDa were found to be products of the proteolytic cleavage. The N-terminus of the G. mellonella PPO was blocked, but eleven partial internal sequences were determined after fragmentation of the purified PPO with trypsin. Three of these peptides exhibited significant homology with highly conserved sequences found in arthopod hemocyanins and insect storage proteins, which indicates that the PPO belongs to this family.
Keywords: Electrophoresis, Polyacrylamide Gel; chymotrypsin; elektroforéza v polyakrylamidovém gelu; Carbohydrates; prekurzory enzymů; Molecular Sequence Data; sacharidy; molekulová hmotnost; molekulární sekvence - údaje; Chymotrypsin; zvířata; Amino Acid Sequence; Hemolymph; Moths; můry; Animals; hemolymfa; katecholoxidasa; Enzyme Precursors; Catechol Oxidase; sekvence aminokyselin; Molecular Weight